Changing of Condylar Fracture Approach in Cipto Mangunkusumo Hospital - Susanto, Imam; Bangun, Kristaninta; Handayani, Siti; Kreshanti, Prasetyanugrahni; Hapsari, Nathania Pudya (Jurnal Plastik Rekonstruksi, 2012)
Management of condylar fracture draws controversy for over three decades. Previously, closed reduction with intermaxillary !xation (IMF) had been predominant for many surgeons, considering shorter length of procedure, ability to achieve preinjury occlusion with acceptable adjustment, and low cost of procedure. Introduction of osteosynthesis material rigid internal !xation (RIF) and adaptive miniplate !xation marked technology development in condylar fracture management and became popular in term of the applicability and outcome results. Over period time, several studies proposed vary classi!cation system and selection patient criteria for surgical treatment on the basis of age, location of fracture, degree of communition, direction of proximal fragment displacement, location of condylar head, concomitant medical illness or associated trauma, and patient’s preferences to achieve optimum goal. This review focuses on the shifting of condylar fracture management at Cipto Mangunkusumo Hospital from 2004-2012.